Perception of electronic filing (e-filing) among tax agents in northern region of Malaysia - Sulaiman, Aryati Juliana; Abd. Khalid, Ahmad Zamil; Ibrahim, Idawati (2005)
Electronic filing is one of electronic services provided by Revenue Board (IRB) in order to assist tax agents in submitting the tax return electronically and as its initiative towards Electronic Government. Besides reducing the cost of printing tax return forms and processing time, it is expected that E-Filing can avoid loss of tax return during submission through mail.This study has been conducted to explore the awareness and the usage of E-Filing among tax agents and to evaluate the respondents’ opinion on the benefits and barriers of using E-Filing. Tax agents in northern region of Malaysia (Kedah, Perlis and Penang) have been chosen as sample of the study.The results showed that the overall mean score for the respondents’ opinion on the benefits of E-Filing is 43.80 compared to the barriers of E-Filing which have overall mean score 35.00. Majority of the respondents realize the advantages of E-Filing may outweigh the disadvantages. This suggests that E-Filing has a great potential of being accepted and used among the tax agents in the future. This is consistent with Social Cognitive Theory and Theory of Planned Behavior which contended that if one belief the outcome of his behavior is beneficial, he is likely to perform the behavior.